Japanese street fashion for young people: A multimodal digital humanities approach for identifying sociocultural patterns and trends - Podlasov, A.; O'Halloran, Kay (Routledge, 2014)
Digital technology has changed the ways research is undertaken in universities and this impact extends to humanities subjects that have traditionally focused on close (pencil and paper type) analysis of exemplar texts. Today, there are new computational and visualization techniques permitting far and close readings of massive repositories of cultural data that are now freely available. These advances are at the heart of the'digital humanities' research paradigm, which brings together computer science, humanities, arts and social science researchers in new institutional structures (eg. specialized research institutes) designed to support such interdisciplinary collaborations.